Level of adult client satisfaction with clinic flow time and services of an integrated non-communicable disease-HIV testing services clinic in Soweto, South Africa: a cross-sectional study - Kathryn L. Hopkins; Khuthadzo E. Hlongwane; Kennedy Otwombe; Janan Dietrich; Mireille Cheyip; Nompumelelo Khanyile; Tanya Doherty; Glenda E. Gray (BMC, 2020)
Abstract Background While HIV Testing Services (HTS) have increased, many South Africans have not been tested. Non-communicable diseases (NCDs) are the top cause of death worldwide. Integrated NCD-HTS could be a strategy to control both epidemics. Healthcare service strategies depends partially on positive user experience. We investigated client satisfaction of services and clinic flow time of an integrated NCD-HTS clinic. Methods This prospective, cross-sectional study evaluated HTS client satisfaction with an HTS clinic at two phases. Phase 1 (February-June 2018) utilised standard HTS services: counsellor-led height/weight/blood pressure measurements, HIV rapid testing, and symptoms screening for sexually transmitted infections/Tuberculosis. Phase 2 (June 2018-March 2019) further integrated counsellor-led obesity screening (body mass index/abdominal circumference measurements), rapid cholesterol/glucose testing; and nurse-led Chlamydia and human papilloma virus (HPV)/cervical cancer screening. Socio-demographics, proportion of repeat clients, clinic flow time, and client survey data (open/closed-ended questions using five-point Likert scale) are reported. Fisher's exact test, chi-square analysis, and Kruskal Wallis test conducted comparisons. Multiple linear regression determined predictors associated with clinic time. Content thematic analysis was conducted for free response data. Results Two hundred eighty-four and three hundred thirty-three participants were from Phase 1 and 2, respectively (N = 617). Phase 1 participants were significantly older (median age 36.5 (28.0-43.0) years vs. 31.0 (25.0-40.0) years; p = 0.0003), divorced/widowed (6.7%, [n = 19/282] vs. 2.4%, [n = 8/332]; p = 0.0091); had tertiary education (27.9%, [n = 79/283] vs. 20.1%, [n = 67/333]; p = 0.0234); and less female (53.9%, [n = 153/284] vs 67.6%, [n = 225/333]; p = 0.0005), compared to Phase 2. Phase 2 had 10.2% repeat clients (n = 34/333), and 97.9% (n = 320/327) were 'very satisfied' with integrated NCD-HTS, despite standard HTS having significantly shorter median time for counsellor-led HTS (36.5, interquartile range [IQR]: 31.0-45.0 vs. 41.5, IQR: 35.0-51.0; p < 0.0001). Phase 2 associations with longer clinic time were clients living together/married (est = 6.548; p = 0.0467), more tests conducted (est = 3.922; p < 0.0001), higher overall satisfaction score (est = 1.210; p = 0.0201). Those who matriculated experienced less clinic time (est = − 7.250; p = 0.0253). Conclusions It is possible to integrate counsellor-led NCD rapid testing into standard HTS within historical HTS timeframes, yielding client satisfaction. Rapid cholesterol/glucose testing should be integrated into standard HTS. Research is required on the impact of cervical cancer/HPV screenings to HTS clinic flow to determine if it could be scaled up within the public sector.